Study on the Impact of Social Media on Marketing Strategies and Tourism Management of Millennial Generation - Afialdi Yonandes; Rahmat Althof; Aulia Ulfa Cheni (CV. HEI PUBLISHING INDONESIA, 2024)
The aim of this study is to examine the impact of social media on marketing strategies and tourism management targeting millennials. Data were collected using a structured online questionnaire distributed to millennials aged 18–40 who had previously used social media to plan or share travel experiences. A total of 200 respondents participated in this study. Secondary data were obtained from relevant literature, including Scopus- and SINTA-indexed journals, industry reports, and previous studies related to social media and tourism. The collected data were analyzed using descriptive statistical analysis and regression analysis. The findings indicate that social media, particularly Instagram and TikTok, plays a significant role in promoting and managing tourism destinations. Furthermore, the integration of social media usage and effective marketing strategies has a synergistic effect in enhancing the quality and attractiveness of tourism destination management. This study highlights the importance of social media-based marketing strategies in strengthening the competitiveness of tourism destinations among millennials.